Alpha‐Lipoic Acid Supplementation Reduces mTORC1 Signaling in Skeletal Muscle from High Fat Fed, Obese Zucker Rats. Issue 12 (1st November 2014) - Li, Zhuyun; Dungan, Cory M.; Carrier, Bradley; Rideout, Todd C.; Williamson, David L.
Abstract: The mammalian target of rapamycin (mTOR) signaling pathway is hyperactive in liver, adipose and skeletal muscle tissues of obese rodents. Alpha‐lipoic acid (αLA) has been well accepted as a weight‐loss treatment, though there are limited studies on its effect on mTOR signaling in high‐fat fed, obese rodents. Therefore, the goal of this study was to determine mTOR signaling and oxidative protein alterations in skeletal muscle of high‐fat fed, obese rats after αLA supplementation. Phosphorylation of the mTOR substrate, eukaryotic initiation factor (eIF) 4E‐binding protein 1 (4E‐BP1) and eIF4B were significantly reduced ( p < 0.05) in muscle from αLA supplemented rats. Activation of AMP‐activated protein kinase (AMPK), an mTOR inhibitory kinase, was higher ( p < 0.05) in the αLA group. Protein expression of markers of oxidative metabolism, acetyl CoA carboxylase (ACC), cytochrome c oxidase IV (COX IV), peroxisome proliferator‐activated receptor (PPAR), and PPAR gamma coactivator 1‐alpha (PGC‐1α) were significantly higher ( p < 0.05) after αLA supplementation compared to non‐supplemented group. Our findings show that αLA supplementation limits the negative ramifications of consuming a high fat diet on skeletal muscle markers of oxidative metabolism and mTORC1 signaling.